Transform the original equation to get less confused with constants
"\\left.EL\\cdot\\frac{d^2y}{dx^2}=P\\cdot y-\\frac{Wx^2}{2}\\right|\\times\\frac{1}{EL}\\longrightarrow\\\\[0.3cm]\ny''=\\overbrace\\frac{P}{EL}^{n^2}\\cdot y-\\overbrace\\frac{P}{EL}^{n^2}\\cdot\\frac{Wx^2}{2P}\\longrightarrow\\\\[0.3cm]\n\\boxed{y''=n^2y-\\frac{Wn^2x^2}{2P}}"
1 STEP: Solve the homogeneous equation
"y''=n^2y\\to[y(x)=e^{kx}\\,\\,\\,\\text{and}\\,\\,\\,y''=k^2\\cdot e^{kx}]\\to\\\\[0.3cm]\nk^2\\cdot e^{kx}=n^2\\cdot e^{kx}\\to\\left[\\begin{array}{c}\n k_1=n\\\\\n k_2=-n\n\\end{array}\\right."
Then,
"\\boxed{y_{hom}(x)=C_1\\cdot e^{nx}+C_2\\cdot e^{-nx}}"
2 STEP: Solve an inhomogeneous equation
To do this, find ANY particular solution, so we will look for it in the form
"y_{par}(x)=Ax^2+Bx+C\\to y''=2A"
Substitute everything in the original equation
"2A=n^2\\cdot\\left(Ax^2+Bx+C\\right)-\\frac{Wn^2x^2}{2P}\\to\\\\[0.3cm]\n\\left(An^2-\\frac{Wn^2}{2P}\\right)x^2+Bn^2x+(Cn^2-2A)=0\\to\\\\[0.3cm]\n\\left\\{\\begin{array}{l}\nAn^2-\\displaystyle\\frac{Wn^2}{2P}=0\\to\\boxed{A=\\frac{W}{2P}}\\\\[0.3cm]\nBn^2=0\\to\\boxed{B=0}\\\\[0.3cm]\nCn^2-2A=0\\to\\boxed{C=\\frac{W}{Pn^2}}\n\\end{array}\\right."
Conclusion,
"\\boxed{y_{par}(x)=\\frac{Wx^2}{2P}+\\frac{W}{Pn^2}}\\\\[0.3cm]\ny_{gen}(x)=y_{hom}(x)+y_{par}(x)\\to\\\\[0.3cm]\n\\boxed{y_{gen}(x)=C_1\\cdot e^{nx}+C_2\\cdot e^{-nx}+\\frac{Wx^2}{2P}+\\frac{W}{Pn^2}}"
To find the constants we will use the boundary conditions
"\\left\\{\\begin{array}{l}y(0)=C_1+C_2+\\displaystyle\\frac{W}{Pn^2}=0\\\\[0.3cm]\ny'(0)=nC_1-nC_2=0\\to C_1=C_2\n\\end{array}\\right.\\longrightarrow\\\\[0.3cm]\n2C_1+\\frac{W}{Pn^2}=0\\to\\boxed{C_1=C_2=-\\frac{W}{2Pn^2}}"
Then,
"y(x)=-\\frac{W}{2Pn^2}\\cdot e^{nx}-\\frac{W}{2Pn^2}\\cdot e^{-nx}+\\frac{Wx^2}{2P}+\\frac{W}{Pn^2}\\to\\\\[0.3cm]\ny(x)=\\frac{W}{2Pn^2}\\cdot\\left(2-\\overbrace{\\left(e^{nx}+e^{-nx}\\right)}^{2\\cosh nx}\\right)+\\frac{Wx^2}{2P}\\to\\\\[0.3cm]\n\\boxed{y(x)=\\frac{W}{Pn^2}\\cdot(1-\\cosh nx)+\\frac{Wx^2}{2P}}"
Comments
Dear Dennis Addo, please use the panel for submitting a new question.
2. A light horizontal strut AB is freely pinned at A and B. It is under the action of equal and opposite compressive force P at its ends and it carries a load W at its centre. Then for 0 < x < 1 2 , EI d2y dx2 + P y + 1 2 W x = 0, given y = 0 at x = 0 and dy dx = 0. Use the Laplace transforms for solving differential equations to show that y = W 2p ( sin ax a cos at 2 2 x), where a2 = p EI
Dear fanni, please use the panel for submitting new questions.
solve the initial value problem x_dx^dy-2y=〖2x〗^4, y(2)=8
Leave a comment